Interplay between bile acids and the gut microbiota promotes intestinal carcinogenesis. Issue 7 (3rd March 2019) - Wang, Sinan; Dong, Wenxiao; Liu, Li; Xu, Mengque; Wang, Yu; Liu, Tianyu; Zhang, Yujie; Wang, Bangmao; Cao, Hailong
Abstract: The gut microbiota and the bile acid pool play pivotal roles in maintaining intestinal homeostasis. Bile acids are produced in the liver from cholesterol and metabolized in the intestine by the gut microbiota. Gut dysbiosis has been reported to be associated with colorectal cancer. However, the interplay between bile acid metabolism and the gut microbiota during intestinal carcinogenesis remains unclear. In the present study, we investigated the potential roles of bile acids and the gut microbiota in the cholic acid (CA; a primary bile acid)‐induced intestinal adenoma‐adenocarcinoma sequence. Apc min/+ mice, which spontaneously develop intestinal adenomas, were fed a diet supplemented with 0.4% CA for 12 weeks. Mice that were fed a normal diet were regarded as untreated controls. In CA‐treated Apc min/+ mice, the composition of the gut microbiota was significantly altered, and CA was efficiently transformed into deoxycholic acid (a secondary bile acid) by the bacterial 7α‐dehydroxylation reaction. The intestinal adenoma‐adenocarcinoma sequence was observed in CA‐treated Apc min/+ mice and was accompanied by an impaired intestinal barrier function and IL‐6/STAT3‐related low‐grade inflammation. More importantly, microbiota depletion using an antibiotic cocktail globally compromised CA‐induced intestinal carcinogenesis, suggesting a leading role for the microbiota during this process. Overall, our data suggested that the crosstalk between bile acids and the gut microbiota mediated intestinal carcinogenesis, which might provide novel therapeutic strategies against intestinal tumor development.